2009
DOI: 10.1590/s1806-83242009000400019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different light-curing devices and aging procedures on composite knoop microhardness

Abstract: The aim of this study was to evaluate the effect of light-curing devices (Halogen/HAL, Light Emitting Diodes/LED, Argon Laser/LAS and Plasma Arc/PAC) and aging procedures (Mechanical Cycling/MC, Thermal Cycling/TC, Storage/S, MC+TC and MC+TC+S) on the micro-hardness of bottom/B and top/T surfaces of 2-mm-high composite resin cylinders. The Knoop microhardness test (25 g, 20 s) on both B and T was performed before and after each aging procedure. For B and T, before aging procedures, PAC showed reduced polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
(25 reference statements)
0
10
0
5
Order By: Relevance
“…16 FS and FZ resins present identical organic matrix compositions, and part of the TEGDMA was replaced by UDMA and BisEMA. 6 These materials present fewer double bonds per unit of weight and diminished conversion of these bonds during polymerization. TCB resin presents a different reactivity to light, due to the presence of organically modified silicate organized in layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 FS and FZ resins present identical organic matrix compositions, and part of the TEGDMA was replaced by UDMA and BisEMA. 6 These materials present fewer double bonds per unit of weight and diminished conversion of these bonds during polymerization. TCB resin presents a different reactivity to light, due to the presence of organically modified silicate organized in layers.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 On the other hand, the broad spectrum of the halogen LCU, extending up to the ultraviolet region (UV-A), can be an advantage to excite coinitiators that absorb shorter wavelengths. 2 The degree of conversion (DC) of methacrylatebased composite resin is influenced not only by light intensity and wavelength, as emitted by the LCU used to excite the photoinitiator molecules, 6 but also by the irradiation time and material composition. 7,8 Moreover, some factors that interfere in light transmission, such as sample thickness, color, translucence, inorganic fillers of composites and the distance between the LCU light tip and the material surface, can also alter this property.…”
Section: Introductionmentioning
confidence: 99%
“…2 This potential problem has been investigated in a number of studies focused on repairing composite resin, which have demonstrated that both the use of an intermediate bonding agent (adhesive and/or silane) and the roughening of the surface of the resin significantly improve the adhesion of the repair. [1][2][3][4][5] Studies have investigated the bonding strength of repairs of aged composites through thermal cycling 2,3,5,6 and immersion in hot water, acids, 2,3 water, or artificial saliva 1,4 for relatively short periods (24 h and 6 mos). [1][2][3][4][5]7 However, studies are needed to determine the behavior of repairs bonded to aged restorations for a longer period of time and the behavior of this repair subjected to the same aging period.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of hardness level also shows the degree of conversion and this is why these tests are crucial [18,19] Traditionally, three main hardness tests were proposed for testing the hardness level of resin composite (Barcol, Knoop and Vickers) [18]. In this study, the Vickers hardness test was used, as done in previous studies [6,7,14].…”
Section: Discussionmentioning
confidence: 99%
“…Low energy consumption during light emitting process is one of the advantages of LEDs and it also enables them to be powered with rechargeable batteries [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%